EVALUASI KAPASITAS PELABUHAN YOS SOEDARSO AMBON-PROVINSI MALUKU: (Yos Soedarso Port Capacity Evaluation Ambon-Maluku Province) - Rumbia, Nuliyati; Tualeka , Napsinur; Assagaf, Sjaid S. Fais (Uniqbu Journal of Exact Sciences, 2022)
As an archipelagic province in eastern Indonesia, the city of Ambon plays an important role in the development of the rate of shipping activity in eastern Indonesia. Yos Yos Soedarso Port Ambon serves shipping and commercial services. This study aims to determine the amount of loading and unloading of goods and the area or container depots available at Yos Soedarso Ambon port, to find out how many passengers get on and off at Yos Soedarso Ambon port and to know how many shipping flow at Yos Soedarso port, Ambon. The method used in this research is descriptive analytical, namely by describing the existing problems sequentially and associated with the factors that support the purpose of the discussion, then analyzed to overcome a problem solving. The results of the study indicate that, the number of unloading 20' containers is 34724 units and the number of unloading 40' containers is 582418 units, the available container unloading area is 21697 m2 in 2020, the number of embarkation and debarkation passengers at Yos Soedarso port Ambon until 2020 is as many as 203006,4 people and 183422.2 people, and the number of ship shipping flows at Yos Soedarso port Ambon until 2020 is foreign ship visits of 197,8852 calls and domestic ship visits of 3165,8680 calls. Keywords: Evaluation, Capacity, Port, Stacking Area